Microbiological quality of cultivation water used for oysters marketed in Cananeia-SP, Brazil - Barbieri, Edison; Bondioli, Ana Cristina; Woiciechovski, Ernani; M. K. Zapotoski, Silvia (O Mundo da Saúde, 2012)
Bivalves represent the environment conditions where oysters are farmed, thus is vital that these organisms are not contaminated because they can represent a serious risk to the public health. This study aimed to assess the microbiological quality of water for the cultivation of oysters of Cooperostra (cooperative of producer) in Cananeia-SP, Brazil. The total and fecal coliforms were analyzed. The results showed that water quality were not satisfactory, according to Brazilian legislation, except for some months. The seasonal interference was analysed and a high positive correlation was verified, with low coliforms concentration in winter. The pluviometric index showed a high positive correlation to the microorganisms analysed.